Prevalence of cultural malpractice during the perinatal period and its determinants among reproductive age women in southwest Ethiopia: A community-based cross-sectional study - Tesfaye Diro, Abinet; Abdissa Fufa, Dinaol; Geremew, Habtamu (Frontiers in Public Health, 2023)
Background: Cultural malpractices are accepted cultural norms and socially shared practices that have a negative impact on health. Cultural malpractices vary in type and number in different communities. This study aimed to determine the prevalence of cultural malpractice during the perinatal period and identify its predictors among reproductive-age women in rural communities of southwestern Ethiopia. Methods: A community-based cross-sectional study was conducted from May 5 to 31, 2019 in Semen Bench district, southwestern Ethiopia; among reproductive-age women who had experienced at least one prior delivery. A systematic random sampling technique was employed to select 422 women for the interview. After collection, the data were entered into EpiData and exported to STATA-14 for further analysis. Descriptive analyses were performed and presented in texts and tables. Besides, binary and multivariable logistic regressions were computed to identify determinants of cultural malpractice. Result: A total of 414 women completed the survey, resulting in a response rate of 98%. We found that 26.33% (95% CI: 22.15%, 30.85%) had food taboos during pregnancy, 31.88% (95% CI: 27.42%, 36.61%) delivered their last child at home, and 33.82% (95% CI: 29.27%, 38.6%) practiced pre-lacteal feeding. Lack of formal education (AOR: 11.22, 95% CI: 6.24, 20.15), lack of ANC follow-up (AOR: 10.82, 95% CI: 5.46, 21.42), rural residence (AOR: 6.23, 95% CI: 2.18, 17.78), and avoiding colostrum (AOR: 21.94, 95% CI: 9.73, 49.48) were significantly associated with cultural malpractice during the perinatal period. Conclusion: The prevalence of cultural malpractice is notably high in the study area. Hence, community-based measures including expansion of education and promotion of maternal health services are important to reduce cultural malpractice during the perinatal period.